2015
DOI: 10.1515/pjvs-2015-0009
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent differences in the effect of early weaning on the chosen hormones secretion in sheep during the postnatal transition to puberty – Preliminary results

Abstract: The influence of early weaning on the cortisol, follicle-stimulating hormone (FSH), luteinizing hormone (LH) and growth hormone (GH) secretion in lambs of both sexes and testosterone (T4) level in male lambs during the postnatal transition to puberty was investigated by radioimmunoassay. It was hypothesized that this influence is long-term and sexually dimorphic. Hence, the effect of weaning at 5 weeks of age in comparison with the weaning at 9 weeks of age on hormone concentrations in peripheral blood plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Furthermore, in lambs weaned at 12 weeks of age an increased release of CRF from the nerve terminals in the median eminence and accumulation of ACTH in the pituitary gland were observed . Cieślak et al (2015) showed a sex-dependent differences in cortisol secretion in lambs subjected to maternal deprivation. In female lambs maternal deprivation caused the stimulation of cortisol secretion in all examinated periods (9 th , 12 th , 16 th week of life).…”
Section: The Hypothalamic-pituitary-adrenal Axis Activity During Matementioning
confidence: 88%
See 2 more Smart Citations
“…Furthermore, in lambs weaned at 12 weeks of age an increased release of CRF from the nerve terminals in the median eminence and accumulation of ACTH in the pituitary gland were observed . Cieślak et al (2015) showed a sex-dependent differences in cortisol secretion in lambs subjected to maternal deprivation. In female lambs maternal deprivation caused the stimulation of cortisol secretion in all examinated periods (9 th , 12 th , 16 th week of life).…”
Section: The Hypothalamic-pituitary-adrenal Axis Activity During Matementioning
confidence: 88%
“…Secretion of the FSH was increased in male lambs after maternal deprivation in all examinated periods, furthermore in female lambs subjected to maternal separation diminished FSH secretion was observed in 9 weeks of age and increased FSH concentration in 12 an 16 weeks of age was noted (Tab. 1) (Cieślak et al 2015). Table 1.…”
Section: Influence Of the Maternal Deprivation On The Hpg Axis Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that bucks had better growth when allowed to suckle for a longer period than those weaned early or abruptly (Palma & Galina, 1995). Besides the impact of growth rate on the age of puberty (Colomer‐Rocher et al., 1987), early weaning results in stress which inhibits the secretions of growth hormone and luteinizing hormone in lambs of both sexes and that of testosterone in male lambs during the postnatal transition to puberty (Chmielewska et al., 2015). Briefly, bucks that attain puberty earlier possess better reproductive capability and shorter generational gaps (Bezerra et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A não diferença quanto às médias de calcificação e seus baixos valores de escore também apontam que não houve situação de degeneração testicular com o passar dos meses (ÜLKER et al, 2005;GOULESTOU, 2017 (CIEŚLAK et al, 2015;NAZARI-ZENOUZ et al, 2016;RECABARREN et al, 2017). Neste caso o tratamento imposto durante a gestação não alterou a testosterona circulante no metabolismo dos animais.…”
Section: Características Do Sêmenunclassified